KUALITAS PELAYANAN TEMPAT PENDAFTARAN PASIEN RAWAT JALAN TERHADAP KEPUASAN PASIEN DI RUMAH SAKIT PROVINSI JAWA BARAT : LITERATURE REVIEW - Shinta Octaviasuni; Widya Ratna Wulan (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
Patient satisfaction at the outpatient registration relates to the hospital health services qualities. West Java Province is one of the reference provinces for the health services  development, but there are still some complaints in the service process and infrastructure such as the lack of patient seats in the outpatient registration. This study aimed to analyze the service quality towards patient satisfaction in outpatient registration at the West Java Province Hospitals by using service quality indicators focusing on tangibles, responsiveness, assurance, reliability, and empathy. The method is a literature review. Data collection by reviewing relevant research journals through the Google Scholar database with keywords using Boolean Operators, namely Service Quality AND Patient Satisfaction AND Outpatient Registration AND Hospitals with 156 journal results. Three journals were selected according to inclusion criteria (West Java area, the year of journals publication range 2017-2020, and an accessible and indexed Indonesian journal). Journal study showed that the outpatient registration patients in West Java Hospitals were quite satisfied with the tangible indicator (physical evidence), responsiveness, and assurance, as well as the reliability  and empathy indicators satisfaction. Patient satisfaction in the outpatient registration at the West Java province hospitals normatively has reached the level of satisfaction of ‘quite satisfied’.